Molecular Mechanisms Behind Vascular Mimicry as the Target for Improved Breast Cancer Management - Wei Y; Jiao Z; Sun T; Lai Z; Wang X (Dove Medical Press, 2023)
Yali Wei,1,* Zheng Jiao,2,* Tianpei Sun,3,* Zhiwei Lai,4 Xiaochun Wang1 1Department of Breast Surgery, Affiliated Hospital of Hebei University, Baoding, Hebei Province, People's Republic of China; 2Department of Neurosurgery, Youanmen Hospital, Beijing, People's Republic of China; 3Clinical School of Medicine, Hebei University, Baoding, Hebei Province, People's Republic of China; 4Department of Thoracic Surgery, Shanghai Sixth People's Hospital Fujian Campus, Jinjiang, Fujian Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaochun Wang, Department of Breast Surgery, Affiliated Hospital of Hebei University, 212 Yuhua Dong Road, Baoding, Hebei Province, 071000, People's Republic of China, Tel +86312-5983922, Email 13903123759@163.comIntroduction: Breast cancer has a high incidence and mortality rate in women due to metastasis and drug resistance which is associated with vasculogenic mimicry (VM). We purposed to explore VM formulation in breast cancer and mechanism of which is involved in EphA2/PIK3R1/CTNNB1 in the present study.Methods: The expression of EphA2/PIK3R1/CTNNB1 and breast cancer patient prognosis was analyzed from TCGA data, both gene and protein expression as well as VM were measured in human breast cancer tissue samples collected in our study. The relationship between EphA2/PIK3R1/CTNNB1 and the formation of VM in breast cancer and its possible regulatory mechanism was explored.Results: The results of the bioinformatics analysis based on TCGA showed that the expression of PIK3R1/ CTNNB1/ PECAM1 (CD31) in tumor tissues was significantly lower than that in normal tissues. EphA2 was positively correlated with PIK3R1, PIK3R1 with CTNNB1, and CTNNB1 with PECAM1 expression in breast cancer tissues. The results of detection in breast cancer and adjacent tissues indicated that the expression of EphA2/PIK3R1/CTNNB1 in cancer tissues was significantly lower than that in adjacent tissues. The expression of PIK3R1 was positively correlated with EphA2 and CTNNB1 expression, respectively, as well as EphA2 expression correlated with CTNNB1 expression positively. VM formation was significantly increased in breast cancer tissues compared with adjacent tissues.Conclusion: Our results suggested that the formation of VM in breast cancer may be related to the EphA2/PIK3R1/CTNNB1 molecular signaling pathway.Keywords: breast cancer, vasculogenic mimicry, EphA2/PIK3R1/CTNNB1 pathway, targeted prediction and prevention